Apolipoprotein A-I mimetics attenuate macrophage activation in chronic treated HIV. (15th March 2021) - Mu, William; Sharma, Madhav; Heymans, Rachel; Ritou, Eleni; Rezek, Valerie; Hamid, Philip; Kossyvakis, Athanasios; Sen Roy, Shubhendu; Grijalva, Victor; Chattopadhyay, Arnab; Papesh, Jeremy; Meriwether, David; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective(s): Despite antiretroviral therapy (ART), there is an unmet need for therapies to mitigate immune activation in HIV infection. The goal of this study is to determine whether the apoA-I mimetics 6F and 4F attenuate macrophage activation in chronic HIV. Design: Preclinical assessment of the in-vivo impact of Tg6F and the ex-vivo impact of apoA-I mimetics on biomarkers of immune activation and gut barrier dysfunction in treated HIV. Methods: We used two humanized murine models of HIV infection to determine the impact of oral Tg6F with ART (HIV + ART + Tg6F + ) on innate immune activation (plasma human sCD14, sCD163) and gut barrier dysfunction [murine I-FABP, endotoxin (LPS), LPS-binding protein (LBP), murine sCD14]. We also used gut explants from 10 uninfected and 10 HIV-infected men on potent ART and no morbidity, to determine the impact of ex-vivo treatment with 4F for 72 h on secretion of sCD14, sCD163, and I-FABP from gut explants. Results: When compared with mice treated with ART alone (HIV + ART + ), HIV + ART + Tg6F + mice attenuated macrophage activation (h-sCD14, h-sCD163), gut barrier dysfunction (m-IFABP, LPS, LBP, and m-sCD14), plasma and gut tissue oxidized lipoproteins. The results were consistent with independent mouse models and ART regimens. Both 4F and 6F attenuated shedding of I-FABP and sCD14 from gut explants from HIV-infected and uninfected participants. Conclusion: Given that gut barrier dysfunction and macrophage activation are contributors to comorbidities like cardiovascular disease in HIV, apoA-I mimetics should be tested as therapy for morbidity in chronic treated HIV.